Chalcohalides: A Rising Type of Second‐Order Nonlinear Optical Materials. Issue 33 (27th October 2022) - Li, Jun; Han, Shan‐Shan; Guo, Sheng‐Ping
Abstract: In the past few decades, many new infrared (IR) second‐order nonlinear optical (NLO) materials have been prepared by various synthetic methods to satisfy the growing market demand. However, few ones have the high potentials to be applicable since their comprehensive NLO properties cannot meet the standards, which include a series of indicators like large NLO effects, high laser‐induced damage thresholds (LIDTs), phase matchability, high thermal stability, good growth habit, and so on. Considering the available IR NLO materials' disadvantages and the market requirements, it is necessary to continuously explore new high‐performance ones. Hitherto, lots of chalcogenides, halides, and oxides have been explored as IR NLO materials. Recently, researchers have found that the combination of two or more structural units into one structure may achieve good NLO properties, as evidenced by the fact that diverse materials with multiple anions are receiving growing interest. Specifically, chalcohalides are highly promising as they may combine the advantages of chalcogenides and halides, viz . large NLO coefficients and wide IR transparency of the former, and large band gaps and high LIDTs of the latter. To address the status of chalcohalides, this review focuses on the newest progresses on this topic (mainly from the last five years), including ternary chalcohalides, quaternary chalcohalides, salt‐inclusion chalcohalides, and rare‐earth chalcohalides. Here we summarize and analyze their compositions, crystal structures, NLO properties, and discuss the structure‐property relationship. Finally, the development prospects for NLO chalcohalides are given. Abstract : This review summarizes the recent progresses on nonlinear optical chalcohalides, which behave as highly promising candidates to respond to the urgent market demand. The contents are organized by the chemical composition of the chalcohalides, and focus on their structures, nonlinear optical properties, and the relationship between them. Finally, an outlook on this topic future is proposed.